Success, Literacy, and Learning: Experiences of Adult Basic Education Students - Shannon Frey (Adult Education Research Conference, 2018)
This qualitative study examines how six Adult Basic Education (ABE) students perceive success. The findings elucidate the connections between students’ and organizations’ notions of success and potential agreements and conflicts.
Keywords: Adult Basic Education; success; GED